Worldwide reduction in MERS cases and deaths since 2016 - Donnelly, CA; Malik, MR; Elkholy, A; Cauchemez, S; Van Kerkhove, MD (Centers for Disease Control and Prevention, 2019)
Since 2012, Middle East respiratory syndrome (MERS) coronavirus has infected 2,442 persons worldwide. Case-based data analysis suggests that since 2016, as many as 1,465 cases and 293-520 deaths might have been averted. Efforts to reduce the global MERS threat are working, but countries must maintain vigilance to prevent further infections.